The Guangzhou YMCA and Vocational Education During the Republican Era - ZHENG Liqun, (Journal of Research for Christianity in China (JRCC), 2025)
The Republic of China's demand for industrial professionals during that era dictated that the Young Men's Christian Association (YMCA) adopted a vocational education-focused approach in its schools, directly leading to the establishment of the Guangzhou YMCA Vocational School. Through its curriculum tailored to societal needs, rigorous standards for faculty, comprehensive administrative measures, and vibrant extracurricular activities, the school attracted a large student body throughout the entire Republican era. It thus contributed significantly to the cultivation of modern vocational talent in Guangdong and demonstrated the YMCA's professional competence in educational endeavors.